Ana Casas & David Roas (ed.), Zona de penumbra: antología del cuento fantástico en el fin de siglo y el modernismo. León: Eolas, 2021. 163 pp. - Gregori, Alfons (Studia Romanica Posnaniensia, 2023)
Ana Casas & David Roas (ed.), Zona de penumbra: antología del cuento fantástico en el fin de siglo y el modernismo. León: Eolas, 2021. 163 pp.